Part 1: Formation and nucleophilic interception of α,β-unsaturated platinum carbenes. Part 2: Efforts toward controlling magnetic properties of cobalt and iron coordination complexes - Ozumerzifon, Tarik J., author; Shores, Matthew P., advisor; Kennan, Alan J., committee member; Neilson, James R., committee member; Achter, Jeffrey D., committee member (Colorado State University. Libraries, 2017)
Presented in this dissertation are a series of studies describing the use of transition metals in several different applications. Part 1 concerns the development of novel platinum(II)-catalyzed reaction manifolds toward C-C bond formation, as well as the formal synthesis of a natural product. Meanwhile, Part 2 describes three separate efforts toward modulation of either single-molecule magnet properties in cobalt(II) or spin state control of iron(II) coordination complexes. The first chapter is a general introduction to single-molecule magnetism (SMM) and spin crossover, as these topics specifically relate to Co(II) and Fe(II) complexes, respectively. The physical origins of both phenomena are discussed, as well as some general terminology that are used throughout Chapters 3-5. Chapter 2 describes the use of Pt(II) salts in alkyne activation reactivity. The vinylogous addition of carbon nucleophiles into α,β-unsaturated platinum carbenes is discussed, and the optimization and scope of enol incorporation is provided. This is followed by a description of how Pt(II) catalysis enables the rapid formal synthesis of frondosin B, a sesquiterpene natural product. In Chapter 3, the synthesis and characterization of several salts of a trigonal prismatic cobalt(II) complex are detailed. The capping ligand used in these podands is cis-,cis-,1,3,5-triaminocyclohexane (tach), a rigid backbone which dictates coordination geometry and the iminopyridine contains pendant tert-butylamide moieties which are meant to enable guest association. The single-molecule magnet behavior (measured via slow magnetic relaxation) of these compounds is also explored, where the cation-binding tetraphenylborate salt shows slow magnetic relaxation at both zero and applied dc fields. A brief discussion of theoretical considerations of the effect of trigonal distortion on axial anisotropy is also presented, which suggests systems in an intermediate twisting geometry may give rise to guest-dependent magnetic properties in SMMs. Chapter 4 presents initial efforts toward the development of an Fe(II) system which can undergo a spin-state switch upon addition of a reagent. The chemoselective process is intended to be the result of an irreversible ligand modification. The first target toward this goal is manifested in desilylation of a 5-siloxy substituted podand. Spectroscopic and spectrometric as well as electrochemical and magnetic data indicate qualitatively that ligand desilylation is occurring as a function of fluoride addition, affecting a decrease in high-spin:low-spin ratio. Last, Chapter 5 details the systematic study of electronic character of 5-pyridyl substitution in the Fe(II) tren iminopyridine tripodal system. The Fe(II) species magnetic susceptibility and Ni(II) analog d-d transition energy data are compared to the Hammett parameter of the respective substituent, which define the complexes' electron-donating or -withdrawing properties. Overall, electron withdrawing substituents at this position lead to stabilization of the HS state. A comparison of these iminopyridine complexes to Fe(II) podands which undergo spin crossover is provided in an effort to explain the observed low-spin behavior of these complexes.